Analyzing Fourth Grade Students’ Narrative Writing Skills Through Serial Image Media - Izah, Zhaviera Zulfa; Cahyaningtyas, Andarini Permata (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study addresses the challenges encountered by fourth-grade students in developing narrative writing skills, a fundamental aspect of Indonesian language education. It investigates the effectiveness of serial image media as an instructional tool and evaluates its impact on the narrative writing performance of students at SDN Mangunsari 01. Employing a descriptive qualitative approach with a case study design, data were collected through classroom observations, semi-structured interviews, and analysis of writing samples from 15 students. The findings reveal that the use of serial image media enhances students’ creativity and supports key narrative elements, including theme development, setting, characterization, plot structure, point of view, paragraph organization, sentence construction, and textual mechanics such as spelling, punctuation, and narrative structure (orientation, climax, resolution). Despite these benefits, students continued to face difficulties with accurate spelling and punctuation. The study concludes that serial image media is a moderately effective strategy for improving narrative writing skills and fostering student engagement. It is recommended that educators integrate this media into language instruction to enrich the writing experience and improve learning outcomes.